10-8x=3(-3x-4)

Simple and best practice solution for 10-8x=3(-3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-8x=3(-3x-4) equation:


Simplifying
10 + -8x = 3(-3x + -4)

Reorder the terms:
10 + -8x = 3(-4 + -3x)
10 + -8x = (-4 * 3 + -3x * 3)
10 + -8x = (-12 + -9x)

Solving
10 + -8x = -12 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
10 + -8x + 9x = -12 + -9x + 9x

Combine like terms: -8x + 9x = 1x
10 + 1x = -12 + -9x + 9x

Combine like terms: -9x + 9x = 0
10 + 1x = -12 + 0
10 + 1x = -12

Add '-10' to each side of the equation.
10 + -10 + 1x = -12 + -10

Combine like terms: 10 + -10 = 0
0 + 1x = -12 + -10
1x = -12 + -10

Combine like terms: -12 + -10 = -22
1x = -22

Divide each side by '1'.
x = -22

Simplifying
x = -22

See similar equations:

| -5=-x+3y | | 9/1-17/5 | | log27x=2/3 | | .2+x=7 | | y+6x=12x-7 | | 30=10(x)+6(x) | | 3y-6=4y | | 4x-24+3x=6x+1 | | 8y=-6x+4 | | 15y=-4-5(1/5) | | 5(n-2)=0 | | x^3=2x^2+3x | | x+x+40+x-50=90 | | 95-73=x | | 2(x-3)+5(-x)=2(-x)-4 | | 3(3+w)=2(w-6) | | 360=x+x-35+.5x+x-46 | | 10/x-2=2 | | X/4-2=16 | | 5y-5+y+31=5y+30-3y | | 0=6t^2-30t+36 | | 2(k+1)-(7+6k)=-5k | | 24-7x=13+4x | | ln(4x-2)+ln(9-3x)=2ln(x+1) | | 2/3y-8=1/6 | | 37-8=X | | (14+2x)(18+2x)=228 | | -3=9+x | | -3=9+8 | | y=8ln(5x) | | (-8)8= | | 5(2a-3)-6(a+2)=-7 |

Equations solver categories